CD302 regulates the malignant phenotypes of lung adenocarcinoma as a tumor suppressor gene - Wang, Kai; Wang, Yao; Lu, Tao; Gao, Manjun; Song, Yongxiang; Chen, Cheng; Ke, Xixian (Frontiers in Oncology, 2025)
BackgroundCD302 encodes a transmembrane glycoprotein involved in immune regulation via cell–extracellular matrix interactions. Its role in lung adenocarcinoma (LUAD) remains unexplored. This study investigates CD302’s expression, clinical relevance, and functional mechanisms in LUAD.MethodsUsing public databases and bioinformatics, CD302 expression and clinical significance were analyzed. Validation was performed in 52 paired NSCLC samples from the Department of Thoracic Surgery at the Affiliated Hospital of Zunyi Medical University using RT−qPCR and clinical correlation analysis. In vitro CD302 overexpression models in A549 and PC-9 cells were used to assess malignant phenotypes.ResultsDatabase analysis revealed that CD302 exhibited low expression in lung adenocarcinoma tissues, with its expression levels being negatively correlated with T stage, N stage, and TNM stage. Patients with high CD302 expression demonstrated significantly higher overall survival (OS) and progression-free survival (PFS). Both univariate and multivariate Cox regression analyses identified CD302 expression as an independent prognostic factor for LUAD patients. A nomogram was constructed to predict 1-, 3-, and 5-year survival rates, and calibration curve analyses confirmed the model’s robust predictive capability. The area under the ROC curve (AUC) of 0.912 further suggests that CD302 holds substantial diagnostic potential. Analysis of clinical NSCLC samples validated the low expression of CD302 in lung adenocarcinoma, with expression levels showing a negative correlation with tumor diameter (correlation coefficient = -0.5358). Moreover, using the human lung adenocarcinoma cell lines A549 and PC-9, a CD302 overexpression model was established. Subsequent CCK-8, colony formation, wound healing, and transwell invasion assays demonstrated that CD302 overexpression inhibits the proliferation, migration, and invasion of NSCLC cells.ConclusionCD302 is expressed at low levels in lung adenocarcinoma tissues, and its expression is negatively correlated with tumor diameter, serving as an independent risk factor for poor prognosis in lung adenocarcinoma patients. Overexpression of CD302 inhibits the proliferation, migration, and invasion of A549 and PC-9 cells. Therefore, CD302 holds potential as a diagnostic and prognostic biomarker for LUAD patients.